2014
DOI: 10.4038/sljid.v4i2.5925
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a rapid immunochromatography assay with an enzyme linked immunosorbent assay (ELISA) for anti-dengue virus IgM detection

Abstract: ObjectivesThe current study was undertaken to compare the sensitivity, specificity, positive predictive value and negative predictive values of a dengue IgM rapid immunochromatography (ICT) assay with a dengue IgM capture ELISA for the detection of anti-dengue virus IgM in patients clinically suspected of having dengue fever (DF). MethodsBlood samples (n=119) were collected from paediatric and adult patients suspected of having DF at Teaching Hospital, Peradeniya (THP) after 5 days of fever. The samples were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…DENV viremia lasts for about 5–6 days followed by the progression to an immunological phase. In Sri Lanka, anti‐DENV IgM and IgG detection after day 5 of the onset of symptoms/fever remains the major laboratory tool to diagnose DENV infection [Senaratne and Noordeen, ; Senaratne et al, ]. Additionally, since dengue is endemic in Sri Lanka, anti‐DENV IgG sero‐positivity is high and anti‐DENV IgM levels may be detected for months following an infection.…”
Section: Introductionmentioning
confidence: 99%
“…DENV viremia lasts for about 5–6 days followed by the progression to an immunological phase. In Sri Lanka, anti‐DENV IgM and IgG detection after day 5 of the onset of symptoms/fever remains the major laboratory tool to diagnose DENV infection [Senaratne and Noordeen, ; Senaratne et al, ]. Additionally, since dengue is endemic in Sri Lanka, anti‐DENV IgG sero‐positivity is high and anti‐DENV IgM levels may be detected for months following an infection.…”
Section: Introductionmentioning
confidence: 99%
“…No significant difference was noted (p [ 0.05) in the accuracy indices for anti-DENV IgM and IgG detection by the ICT assay between the DF and DHF patients ( Table 3). A recent study conducted by Senaratne et al in a different region of Sri Lanka tested only 119 samples for anti-DENV IgM and IgG and incidentally this study also has used the same ELISA (Panbio Diagnostics, Australia) for validating a different ICT assay [8]. The sensitivity, specificity and the PPV of the ICT assay used by Senaratne et al for anti-DENV IgM detection were higher than those observed in the current study indicating the differences in the accuracy indices of different ICT assays.…”
mentioning
confidence: 99%
“…Moreover, the difference between different ICT assays for detecting a particular marker using the same ELISA comparator indicates the importance of validating rapid ICT assays. Previous studies report a wide variation in the detection sensitivity and specificity ranging from 20 to 100% for the detection of anti-DENV IgM and anti-DENV IgG for some commercially available rapid ICT assays [2,3,5,6,8]. Moreover, sensitivity of anti-DENV IgM detection is significantly low in secondary infections [10] and thus the low sensitivity for anti-DENV IgM detection by the ICT assay in the current study is not surprising, as more than 60% of the study sample had secondary DENV infections.…”
mentioning
confidence: 99%
See 1 more Smart Citation